2018
DOI: 10.1007/s00232-018-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Enriched Archaeosomes as a Molecular System for Studying Interactions of Cholesterol-Dependent Cytolysins with Membranes

Abstract: Archaeosomes are vesicles made of lipids from archaea. They possess many unique features in comparison to other lipid systems, with their high stability being the most prominent one, making them a promising system for biotechnological applications. Here, we report a preparation protocol of large unilamellar vesicles, giant unilamellar vesicles (GUVs), and nanodiscs from archaeal lipids with incorporated cholesterol. Incorporation of cholesterol led to additional increase in thermal stability of vesicles. Surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Other possibilities for prospective studies include the addition of PEG-linked lipids and the subsequent formation of mixed vesicles, which might have better in vivo stability compared with the pure formulation, due to the lower proportion of archaeal lipid and the additional in vivo stabilization effect of certain lipids, especially those already used in clinical applications (e.g., PEG lipids, binary sphingomyelin/cholesterol formulations). 31 In addition, archaeosomes derived from diether lipids of A. pernix could be used as a system for controlled drug delivery, as it has been shown that intact archaeosomes that are endocytosed release their charge on demand by nanosecond electroporation, 28 provided they have sufficient biological stability to reach the target site. Ultimately, mixed formulations have unpredictable behavior and therefore require thorough characterization studies aimed at finding optimal lipid ratios for potential applications that exhibit the best physicochemical stability and stability in biological systems.…”
Section: ■ Conclusion and Future Outlookmentioning
confidence: 99%
“…Other possibilities for prospective studies include the addition of PEG-linked lipids and the subsequent formation of mixed vesicles, which might have better in vivo stability compared with the pure formulation, due to the lower proportion of archaeal lipid and the additional in vivo stabilization effect of certain lipids, especially those already used in clinical applications (e.g., PEG lipids, binary sphingomyelin/cholesterol formulations). 31 In addition, archaeosomes derived from diether lipids of A. pernix could be used as a system for controlled drug delivery, as it has been shown that intact archaeosomes that are endocytosed release their charge on demand by nanosecond electroporation, 28 provided they have sufficient biological stability to reach the target site. Ultimately, mixed formulations have unpredictable behavior and therefore require thorough characterization studies aimed at finding optimal lipid ratios for potential applications that exhibit the best physicochemical stability and stability in biological systems.…”
Section: ■ Conclusion and Future Outlookmentioning
confidence: 99%
“…Unilamellar vesicles can be made by sonication [ 26 ], extrusion [ 27 ] and the electroformation method [ 28 , 29 ]. The latter makes giant unilamellar vesicles (GUVs, ~10–150 μm) for microscopy studies or as reaction vessels [ 28 , 29 ]. Unilamellarity of tetraether archaeosomes made by the extrusion method was confirmed by the observation of only single rings in the freeze-fracture micrographs [ 30 ] and a single layer (~5 nm in thickness) in electron cryotomography [ 31 ].…”
Section: Vesicular Archaea Lipid Membranes (Archaeosomes)mentioning
confidence: 99%
“…In terms of therapeutics delivery, archaeosomes are favored over conventional Like conventional liposomes, archaeosomes can be prepared as multilamellar and unilamellar vesicles with varying sizes. Unilamellar vesicles can be made by sonication [26], extrusion [27] and the electroformation method [28,29]. The latter makes giant unilamellar vesicles (GUVs, ~10-150 µm) for microscopy studies or as reaction vessels [28,29].…”
Section: In Vitro Stability Of Tetraether Archaeosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this Special Issue, three contributions bring new insights into how the presence of cholesterol alters physicochemical properties of lipid membranes: Rezelj et al (2018) report a protocol to prepare lipid vesicles and nanodiscs containing archaeal lipids and cholesterol, and extensive biophysical studies to characterize the vesicles and the binding to these vesicles of two different cytolysins-toxins whose pore-forming properties depend on the presence of cholesterol. The high stability of the vesicles made of archaeal lipids is suggested to render them attractive for biotechnology applications and for studies of membrane/protein interactions.…”
mentioning
confidence: 99%